Characterization of anaphylaxis reveals different metabolic changes depending on severity and triggers. Issue 10 (2nd August 2021) - Perales‐Chorda, Carolina; Obeso, David; Twomey, Laura; Rojas‐Benedicto, Ayelén; Puchades‐Carrasco, Leonor; Roca, Marta; Pineda‐Lucena, Antonio; Laguna, José Julio; Barbas, Coral; Esteban, Vanesa; Martí‐Garrido, Jaume; Ibañez‐Echevarria, Ethel; et al.
Abstract: Background: Despite the increasing incidence of anaphylaxis, its underlying molecular mechanisms and biomarkers for appropriate diagnosis remain undetermined. The rapid onset and potentially fatal outcome in the absence of managed treatment prevent its study. Up today, there are still no known biomarkers that allow an unequivocal diagnosis. Therefore, the aim of this study was to explore metabolic changes in patients suffering anaphylactic reactions depending on the trigger (food and/or drug) and severity (moderate and severe) in a real‐life set‐up. Methods: Eighteen episodes of anaphylaxis, one per patient, were analysed. Sera were collected during the acute phase (T1), the recovery phase (T2) and around 2–3 months after the anaphylactic reaction (T0: basal state). Reactions were classified following an exhaustive allergological evaluation for severity and trigger. Sera samples were analysed using untargeted metabolomics combining liquid chromatography coupled to mass spectrometry (LC‐MS) and proton nuclear magnetic resonance spectroscopy ( 1 H‐NMR). Results: 'Food T1 vs T2' and 'moderate T1 vs T2' anaphylaxis comparisons showed clear metabolic patterns during the onset of an anaphylactic reaction, which differed from those induced by drugs, food + drug or severe anaphylaxis. Moreover, the model of food anaphylaxis was able to distinguish the well‐characterized IgE (antibiotics) from non‐IgE‐mediated anaphylaxis (nonsteroidal anti‐inflammatory drugs), suggesting a differential metabolic pathway associated with the mechanism of action. Metabolic differences between 'moderate vs severe' at the acute phase T1 and at basal state T0 were studied. Among the altered metabolites, glucose, lipids, cortisol, betaine and oleamide were observed altered. Conclusions: The results of this exploratory study provide the first evidence that different anaphylactic triggers or severity induce differential metabolic changes along time or at specific time‐point, respectively. Besides, the basal status T0 might identify high‐risk patients, thus opening new ways to understand, diagnose and treat anaphylaxis. Abstract : For the first time, the metabolic profile of anaphylaxis in a real‐life set‐up was characterized and provide evidence that different triggers (Food and Drug) and severity (Moderate and Severe) induce differential metabolic changes improving clinical practice. Eighteen episodes of anaphylaxis with a full clinical characterization were analyzed by metabolomics. The time points were: acute phase (T1), recovery phase (T2) and basal state (T0). Basal status might identify high risk patients, thus opening new ways to understand, diagnose and treat anaphylaxis